OVERVIEW OF THE BANDWAGON EFFECT PHENOMENON IN ADOLESCENTS - Romadhoni, Zaidan Aufi; Ansyah, Eko Hardi (Journal of Social Science, 2025)
Objective: This study will focus on exploring the picture of the bandwagon effect phenomenon in adolescents. Method: The location of the study was at SMA Muhammadiyah 2 Sidoarjo, using 3 subjects from students at the school. The research process uses qualitative methods with a descriptive phenomenological approach. The use of this method aims to be able to explore deeper personal experiences of each subject, to then be analyzed and interpreted in depth. The data collection process was carried out by applying interviews guided by three aspects of the bandwagon effect, namely conformity, interpersonal influence, and status seeking. Results: Based on this process, it was found that aspects of conformity and interpersonal influence had a more dominant influence on the subject's decision to follow the trend without consideration, when compared to one other aspect, namely the status of seeking. In addition, results were also quite varied related to the impact of the bandwagon effect, which consisted of negative impacts and positive impacts from following the trend activities carried out by the subject. Novelty: This study highlights a phenomenological exploration of how adolescents are influenced by different aspects of the bandwagon effect—specifically comparing the dominance of conformity and interpersonal influence over status seeking—in a real-world school context.